Life cycle assessment of common reed (Phragmites australis (Cav) Trin. ex Steud) cellulosic bioethanol in Jiangsu Province, China. (September 2016) - Shuai, Wenjuan; Chen, Ning; Li, Bin; Zhou, Dongmei; Gao, Juan
Abstract: Common reed ( Phragmites australis (Cav) Trin. ex Steud ) at wetlands is a natural resource in Jiangsu Province, China. Proper application of common reed could supplement bioenergy feedstocks and encourage wetlands conservation in this area. In this study, common reed and soil samples from wetlands near to farm, coastline and for wastewater treatment were collected. Potential bioethanol yield was estimated based on biomass yield and bioethanol production, and a life cycle assessment (LCA) model was built to analyze environmental performance of common reed bioethanol. The dry biomass yield of common reed was in the range of 3.8–36 Mg ha −1, and location was the significant factor on biomass yield. Soil pH and available N content had positive impacts on yields of biomass and bioethanol; higher glucan content was detected in stem than in leaf and flower, while ash and klason lignin contents were higher in leaf than in stem and flower. The results indicated that wetlands with high available N content were very suitable for common reed growth, and stem fraction was better than leaf for bioethanol production. Based on LCA model calculation, the net energy and ratio of energy efficiency were compatible to bioethanol from switchgrass and rice straw, and the greenhouse gases (GHG) emission intensity and eutrophication potential were 15 gCO2, eq MJ −1 and −1.1 gPO4 3− eq MJ −1 . The results indicate that common reed is a sustainable and renewable resource for bioethanol production, especially those grown on wetlands near to farmland in Jiangsu Province, China. Highlights: Higher soil pH and available N content increased common reed biomass yield. Soil properties did not change polysaccharide contents in common reed. Bioethanol based on common reed can produce positive net energy. Common reed bioethanol has negative eutrophication potential.